Diversity, Antimicrobial Activity, and Antibiotic Susceptibility Pattern of Endophytic Bacteria Sourced From Cordia dichotoma L - Sharma, Mahima; Mallubhotla, Sharada (Frontiers in Microbiology, 2022)
Endophytic bacteria isolated from medicinal plants are crucial for production of antimicrobial agents since they are capable of possessing bioactive compounds with diverse structure and activities. Cordia dichotoma a plant of medicinal importance native of Jammu region of India was selected for isolation and characterization of culturable endophytic bacteria and evaluation of their antimicrobial activities. Standardized surface sterilization methods were employed to isolate thirty three phenotypically distinguishable endophytic bacteria from the root, stem, and leaf parts of the plant. Shannon Wiener diversity index clearly divulged diverse endophytes in roots (0.85), stem (0.61) and leaf (0.54) tissues. Physio-biochemical features of the isolates differentiated the distinct variations in their carbohydrate utilization profile and NaCl tolerance. The endophytes produced an array of enzymes viz. catalase, oxidase, amylase, cellulase, nitrate reductase and lipase. The bacterial isolates belong to the genera Bacillus, Pseudomonas, Paenibacillus, Acidomonas, Streptococcus, Ralstonia, Micrococcus, Staphylococcus, and Alcalignes predominantly. However, the antibiotic susceptibility pattern indicated the isolates were mostly sensitive to erythromycin and streptomycin, while resistant to rifampicin, amoxicillin and bacitracin. Interestingly, majority of the bacterial endophytes of C. dichotoma showed antimicrobial activity against Bacillus subtilis followed by Klebsiella pneumoniae. The 16S rRNA sequence of Bacillus thuringiensis has been deposited in the NCBI GenBank database under accession number OM320575. The major compounds of the crude extract derived from endophytic Bacillus thuringiensis OM320575, according to metabolic profile examination by GC-MS are Dibutyl phthalate, Eicosane, Tetrapentacontane, Heneicosane, and Hexadecane, which possessed antibacterial activities. In conclusion, results indicated the potential of C. dichotoma to host a plethora of bacterial endophytes that produce therapeutic bioactive metabolites.